150 KeV Cu- ion- implantation in SrVO3 thin films: A study of Cu induced defect states - Saraswat, Himani; Chaudhary, Surekha; Varshney, Mayora; Devi, Devarani; Singh, Fouran; Won, S. O.; Shin, Hyun-Joon; Sharma, Aditya (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Investigations on the extrinsic defects induced alteration in B-O6 octahedra, energy band-structure amendments and physical assets of ABO(3) perovskites are technologically important and require modest approaches for the defect creation and their investigations. In this study, Cu defects have been assimilated in SrVO3 films using 150 KeV Cu ion-implantation with two different ion fluences; 1.63 x 10(15) ion/cm(2) and 8.15 x 10(15) ion/cm(2). The implanted Cu ions do not make metallic/oxide clusters in SrVO3 films, as confirmed by XRD studies, but have facilitated the lattice parameter enlargement and energy band-gap narrowing by creating their defect states and V-O6 octahedra distortion. NEXAFS spectra at Cu L-edge have confirmed the Cu2+ ions in low/high Cu doses implanted SrVO3 films. Cu defects induced V-O6 octahedra distortion has manifested a diverse ligand field interaction between V 3 d and O 2p orbitals and has narrowed the; (i) energy gap of V 2p(3/2) and V 2p(1/2) transitions and (ii) energy gap between t(2g)/e(g) and the O 2p and metal (n+1)sp hybridized orbitals, leading to the band-structure alteration of SrVO3 films. Mechanistic understanding of band-structure perturbation is discussed in the light of ion-solid interaction induced defect formation in SrVO3 thin films.
Keywords: RAY-ABSORPTION SPECTROSCOPY; OPTICAL-PROPERTIES; MECHANISTIC INSIGHTS; TIO2 NANOPARTICLES; GRAIN-GROWTH; CERAMICS; SRTIO3; XANES; PURE; SIZE